The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1016/j.schres.2007.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Developmental trajectories of brain structure in adolescents with 22q11.2 deletion syndrome: A longitudinal study

Abstract: The 22q11.2 deletion syndrome (22q11.2DS) is associated with very high rates of schizophrenialike psychosis and cognitive deficits. Here we report the results of the first longitudinal study assessing brain development in individuals with 22q11.2DS. Twenty-nine children with 22q11.2DS and 29 age and gender matched controls were first assessed during childhood or early adolescence; Nineteen subjects with 22q11.2DS and 18 controls underwent follow-up during late adolescenceearly adulthood. The 22q11.2DS subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
83
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 45 publications
(71 reference statements)
7
83
2
Order By: Relevance
“…This could be due to a plateau in the compensatory drive or a decrease in myelination/fiber size with age. One longitudinal study reported an increase in cranial white matter in children with 22q11DS over time, 15 but there were no CC measurements in this study or others, 38 and thus the trajectory of CC development in 22q11DS remains unknown.…”
Section: Discussionmentioning
confidence: 56%
“…This could be due to a plateau in the compensatory drive or a decrease in myelination/fiber size with age. One longitudinal study reported an increase in cranial white matter in children with 22q11DS over time, 15 but there were no CC measurements in this study or others, 38 and thus the trajectory of CC development in 22q11DS remains unknown.…”
Section: Discussionmentioning
confidence: 56%
“…As noted, no differences were observed in brain volumes between the 7 psychotic and 12 nonpsychotic patients with 22qDS studied prospectively with MRI scans and compared with normal controls [21]. There was also no evidence of the accelerated decrease in cortical gray matter volume commonly reported in other samples at high risk for schizophrenia.…”
Section: Possible Risk and Predictive Factors For Schizophrenia Exprementioning
confidence: 66%
“…There was also no evidence of the accelerated decrease in cortical gray matter volume commonly reported in other samples at high risk for schizophrenia. The decrease in volume (pruning) of the superior temporal gyrus gray matter usually seen in normal adolescent development was not observed in 22qDS, possibly due to delayed maturation [21]. The significance of the results from this cohort study is limited by the small sample size, possible ascertainment bias of patients referred for a psychiatric study, factors selected for investigation, and the young age of nonpsychotic patients at follow-up.…”
Section: Possible Risk and Predictive Factors For Schizophrenia Exprementioning
confidence: 70%
See 2 more Smart Citations